Membrane-bound IL-15 co-expression powers a potent and persistent CD70-targeted TRuC T-cell therapy - Webb, Lindsay; Lofgren, Michael; Patterson, Troy; Watt, Amy; Lajoie, Jason; Zieba, Adam; Fleury, Michelle; Liu, Erica; Ding, Jian; Tighe, Robert (Frontiers in Immunology, 2025)
IntroductionAlthough T-cell immunotherapies have been effective in the treatment of hematological malignancies, solid tumors have proven challenging due to the immunosuppressive microenvironment and lack of viable target antigens. The immune checkpoint ligand CD70, overexpressed in several solid tumors, yet with limited expression in healthy tissue, has emerged as a promising immunotherapeutic target.MethodThis study describes the generation and preclinical characterization of ADP-520, a high-affinity, fratricide-resistant, CD70-targeted T-cell receptor fusion construct (TRuC) T-cell therapy enhanced with constitutively expressed mbIL-15, a membrane-bound fusion protein comprising interleukin-15 (IL-15) linked to full-length IL-15 receptor-alpha. The phenotypic distribution, expansion and persistence of ADP-520 TRuC T cells were measured in vitro under autonomous and antigen-dependent conditions, with the contributions of TCR and IL-15 signaling pathways ascertained using inhibition assays. Chronic antigen stimulation was used to evaluate exhaustion-resistance, while anti-tumor potency was explored both in vitro and in vivo.ResultsADP-520 was found to have potent and antigen-specific activity against hematological and solid CD70-expressing tumors, without apparent fratricide or killing of bystander T cells despite CD70 expression by activated lymphocytes. Engineered co-expression of mbIL-15 augmented antigen-dependent expansion through pro-survival effects and enrichment of an early memory T-cell phenotype, thus enhancing tumor-autonomous, exogenous cytokine-free persistence and bolstering exhaustion resistance during chronic stimulation. mbIL-15 co-expression also enhanced intratumoral T-cell infiltration in vivo for potent and persistent antitumor efficacy.DiscussionThese findings characterize ADP-520 as a first-in-class, CD70-targeted, fratricide-resistant autologous TRuC T-cell therapy leveraging native TCR signaling combined with constitutive IL-15 signaling to impart T cells with enhanced persistence, tumor penetration, and antitumor efficacy. This makes ADP-520 a promising cell immunotherapy candidate for clinical development, with the potential to overcome hurdles intrinsic to the treatment of solid tumors.